Effect of CO{60} Gamma Radiation on Material Surface Properties for Layer-by-Layer Laser Sintering; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Gradoboev A. V. Aleksandr Vasilyevich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen